Beliefs about food allergies in adolescents aged 11–19 years: A systematic review. Issue 4 (6th April 2022) - Newman, Kristina L.; Chater, Angel; Knibb, Rebecca C.
Abstract: Aims: Research suggests of people with food allergy (FA), adolescents have the highest risk of fatal allergic reactions to food, yet understanding of this population and how they manage their condition is limited. Understanding beliefs and how they affect behaviour could inform ways to reduce risk taking behaviour and fatal reactions in adolescents. This systematic review aimed to explore beliefs adolescents hold about their FA, and how these may be associated with FA management. Demographics: Adolescents aged 11–19 years with FA. Methodology: A systematic search of seven databases was conducted. Papers of any design were included that reported on the beliefs about FA in adolescents aged 11–19 years. Data was systemised by narrative thematic analysis. Findings: 20 studies were included. Themes included navigating FA in different environments, carriage and use of adrenaline auto‐injectors, management of the risk of anaphylaxis, behaviour and understanding of others, and food‐allergic identity. Implications: Adolescents with FA hold a variety of condition beliefs; some beliefs were related to behaviour that could lead to an allergic reaction, while other beliefs were related to protective behaviours. Further research into understanding adolescent beliefs in order to inform clinical management and reduce the risk of potential fatal reactions is essential.